Effects of perioperative cognitive function training on postoperative cognitive dysfunction and postoperative delirium: a systematic review and meta-analysis - Zhao, Li; Zhu, Hongyu; Mao, Wei; Zhou, Xuelei; Xie, Ying; Li, Linji (Frontiers in Neurology, 2023)
Background: It is not known whether perioperative cognitive training reduces the incidence of perioperative neurocognitive disorders. We therefore performed a meta-analysis to assess the effect of perioperative cognitive training on the incidence of perioperative neurocognitive impairment. Methods: We conducted a systematic search of Cochrane, Pubmed, Embase and Web of Science to identify randomized controlled trials and cohort studies reporting the association between perioperative cognitive training and perioperative neurocognitive disorders. The search cut-off date was August 2022 and there were no language restrictions. Search, data extraction and quality assessment were conducted independently by two researchers. Results: The study included 9 clinical trials with a total of 975 patients. The results showed that perioperative cognitive training significantly reduced the incidence of postoperative cognitive dysfunction postoperative delirium (POCD) compared with the control group (RR=0.5, 95%CI: 0.28-0.89, P=0.02). For the incidence of postoperative delirium (POD) the difference between the two groups was not statistically significant. In addition, the cognitive training group had less postoperative decline in MMSE scores, but there was no difference in length of hospital stay. Regarding treatment compliance, the proportion of patients in the cognitive training group who completed the pre-determined length of training was 14%. Conclusion: Perioperative cognitive training significantly reduced the incidence of POCD, but the difference in the incidence of POD was not statistically significant.